The interaction of ethylene with free gold cluster cations: infrared photodissociation spectroscopy combined with electronic and vibrational structure calculations. (22nd November 2018) - Lang, Sandra M; Bernhardt, Thorsten M; Bakker, Joost M; Yoon, Bokwon; Landman, Uzi
Abstract: The interaction of ethylene with free gold clusters of different sizes and charge states has been previously shown theoretically to involve two different adsorption modes of the C2 H4 molecule, namely: the di- σ - and π -bonded ethylene adsorption configurations. Here, we present the first experimental investigation of the structure of a series of gas-phase gold-ethylene complexes, . By employing infrared multiple-photon dissociation spectroscopy in conjunction with first-principles calculations it is revealed that up to three C2 H4 molecules preferably bind to gold cations in a π -bonded configuration. The binding of all ethylene molecules is found to be dominated by partial electron donation from the ethylene molecules to the gold clusters leading to an activation of the C–C bond. The cooperative action of multiple coadsorbed C2 H4 on is shown to enable additional charge back-donation and an enhanced C–C bond activation. In contrast, the strong C–H bond is not weakened and the experimental spectra do not give any indication for C–H bond dissociation. The possible correlations of the C–C bond stretch vibration with the C–C bond length and the net charge transfer are discussed.